1995
DOI: 10.1002/ajmg.1320600604
|View full text |Cite
|
Sign up to set email alerts
|

Family patterns of developmental dyslexia, part II: Behavioral phenotypes

Abstract: The motor control of bimanual coordination and motor speech was compared between first degree relatives from families with at least 2 dyslexic family members, and families where probands were the only affected family members. Half of affected relatives had motor coordination deficits; and they came from families in which probands also showed impaired motor coordination. By contrast, affected relatives without motor deficits came from dyslexia families where probands did not have motor deficits. Motor coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 44 publications
8
30
0
Order By: Relevance
“…For example, Bakker [31]has suggested that children with reading impairments have difficulty with the sequential reproduction of ordered stimuli and that this deficit in recall is present for auditory, visual and haptic stimuli. This observation is also consistent with the work of Wolff et al [32, 33]. They showed that impairments intemporal processing are not limited to sensory-perceptual tasks and can be manifest on simple motor-sequencing tasks as well.…”
Section: Discussionsupporting
confidence: 93%
“…For example, Bakker [31]has suggested that children with reading impairments have difficulty with the sequential reproduction of ordered stimuli and that this deficit in recall is present for auditory, visual and haptic stimuli. This observation is also consistent with the work of Wolff et al [32, 33]. They showed that impairments intemporal processing are not limited to sensory-perceptual tasks and can be manifest on simple motor-sequencing tasks as well.…”
Section: Discussionsupporting
confidence: 93%
“…Lashley (1951) proposed that neural mechanisms responsible for timing precision and serial order control underlie both language production and skilled movement. In line with this hypothesis, and consistent with findings in children with dyslexia (Wolff, Melngailis, Obregon, & Bedrosian, 1995), Bishop (2002) suggested that a deficit in timing precision (i.e., the ability to keep time with relatively low levels of variability) underlies both the language and motor deficits seen in children with SLI. Timing deficits also may be predicted on the basis of prosodic difficulties apparent in children with SLI (Gerken & McGregor, 1998;Goffman, 1999Goffman, , 2004McGregor & Leonard, 1994).…”
Section: Timing and The Procedural Deficit Hypothesissupporting
confidence: 82%
“…In the dyslexia literature, several studies have reported timing control deficits in bimanual coordination tasks with half of the participants with dyslexia affected (Wolff, 1993;Wolff, Michel, Ovrut, & Drake, 1990;Wolff et al, 1995). Given that SLI and dyslexia are often comorbid (Snowling, 2012), and procedural learning deficits have been implicated in children with SLI, it is reasonable to hypothesize that bimanual coordination is impaired in children with SLI.…”
Section: Bimanual Clappingmentioning
confidence: 99%
“…It is important to stress that Wolff et al [1995] measured precision of motor timing in a task where the child was required to tap in time to a metronome and continue at the same rate after the metronome stopped. In contrast, the current studies used simpler speeded motor tasks.…”
Section: Discussionmentioning
confidence: 99%